The Role of Educators in Improving Learning Quality at the Police Academy - Eko Krismianto; Suwito Eko Pramono; Rodiyah (Universitas Negeri Semarang, 2026)
Police education plays a strategic role in developing professional, ethical, and competent human resources within the Indonesian National Police (Polri) to address the dynamics of modern policing. The Police Academy (Akpol), as a higher education institution, is required to provide quality education, where the role of educators is a key factor in the success of the educational process. This study aims to examine in depth the role of educators in improving the quality of learning at the Police Academy, identify the obstacles faced, and analyze the strategies applied in efforts to improve the quality of learning. This study uses a qualitative approach with a case study design. The research participants consisted of educators and Akpol cadets from Levels I to III. Data collection techniques included in-depth interviews, participatory observation, and documentation studies. The data obtained were analyzed using thematic analysis. The results showed that educators at the Police Academy have a multidimensional role, not only as teachers but also as facilitators, mentors, motivators, and role models in shaping cadets' academic competence, professional skills, and attitudes of discipline and leadership. However, several obstacles were found in the implementation of learning, including limited variety of learning methods, suboptimal use of technology, the dual workload of educators, and limited supporting facilities and infrastructure. To overcome these obstacles, educators applied contextual learning strategies, field experience-based learning, and competency development through training and certification. This study concludes that improving the quality of learning at the Police Academy requires the support of sustainable institutional policies, particularly in strengthening the competence of teaching staff and providing adequate learning facilities.